Nurses' perceptions on the effects of high nursing workload on patient care in an intensive care unit of a referral hospital in Malawi: a qualitative study - Zione Banda; Mirriam Simbota; Chimwemwe Mula (BMC, 2022)
Abstract Background The Malawi health system has taken numerous actions to reduce high nurse workloads, despite this, shortage of nurses especially in critical care settings still persists due to lack of prioritisation of critical care. Therefore, it is important to understand the effects of high nursing workload in Intensive Care Unit (ICU). This study aimed at exploring the perceptions of nurses regarding the effects of high nursing workload on patient care in ICU at Queen Elizabeth Central Hospital. Methods This qualitative descriptive study was conducted in a general ICU at Queen Elizabeth Central Hospital in Blantyre, Malawi. A purposive sample of 12 nurses working in the ICU was selected. Participants included full-time nurses working in the ICU. A total of 10 In-depth interviews were conducted to collect data upon which data saturation was reached. A semi-structured interview guide was used for data collection. Data was analysed manually using thematic analysis method by Braun & Clarke. Results Study findings indicated that high nursing workload compromises the delivery of quality nursing care to critically ill patients, compromises patient safety and has negative impact on nurses' wellbeing. Conclusion The study findings portray that nurses are aware of the negative effects that high nursing workload has on patient care. The study findings support the need for more ICU nurses in order to reduce nurse workloads and the need for nurse managers and policy makers to develop strategies to manage nurse workloads and its effects on patient care.